Al-Qur - Bilhaq, M. Agus Muhtadi; Rohmaniyah, Inayah; Rahmatullah, Salim (Faculty of Ushuluddin, Adab, and Da'wah, State Islamic University of Palangka Raya, 2023)
The minor resurrection (qiyamah al-sugra) was generally interpreted as the death of an individual human being, meaning that when a person dies, his or her resurrection has arisen. However, in the tafsir entitled Kiamat dalam Perspektif Al-Qur